Impact of Diabetes Mellitus on Lower Urinary Tract Symptoms in Benign Prostatic Hyperplasia Patients: A Meta-Analysis - Xin, Caihong; Fan, Huaying; Xie, Jing; Hu, Jingcheng; Sun, Xin; Liu, Qiuchen (Frontiers in Endocrinology, 2022)
Background: Benign prostatic hyperplasia (BPH) is a disease that causes lower urinary tract symptoms (LUTS), which are the most common urological problem in approximately one-third of the male population aged over 50 years. Some studies have suggested that diabetes may be a risk factor for the development of BPH. However, whether diabetes aggravates the LUTS of BPH patients is still controversial. Aim: To investigate the impact of diabetes mellitus on LUTS in BPH patients. Methods: A literature search was conducted using Web of Science, Embase, PubMed, and China National Knowledge Infrastructure literature databases. This meta-analysis was registered in PROSPERO (registration number: CRD 42020200794). Fixed- or random-effects models were used for analysis according to heterogeneity. The results of the systematic analysis are presented as weighted mean difference (WMD) with the corresponding 95% confidence intervals (CI). Results: In total, 1308 studies were retrieved from databases and 18 articles comprising 1685 cases and 4653 controls were selected for meta-analysis. The results of the meta-analysis showed that the IPSS value and prostate volume of BPH patients with diabetes was significantly higher than that of BPH patients without diabetes. Conclusions: This systematic review is the first to evaluate the impact of diabetes mellitus on LUTS in BPH patients. The results of our meta-analysis support the hypothesis that LUTS in BPH patients is increased in patients with diabetes mellitus compared with controls, which suggests that physicians should pay more attention to BPH patients with diabetes mellitus.